ANALISIS OVERALL EQUIPMENT EFFECTIVENESS (OEE) PADA WEBSITE TELCO TOWER LAND LEASE - Alhady, Muhamad Irfan; Asri Wulandari; Yasir Ahmad Abdillah (Website, 2024)
In the fast-paced digital era, the telecommunications sector continues to rapidly evolve. Telecommunication towers are essential infrastructures for providing connectivity and effective communication. However, the management and leasing of land for telecommunication towers face challenges such as complex processes and a lack of integrated information systems, necessitating a system that can effectively manage land leases. Therefore, this research aims to design and develop a web-based Telco Tower Land Lease Information System as a solution to address the land lease data processing issues. This information system allows users to easily and efficiently manage land leases and access relevant information regarding telecommunication towers. The evaluation of the developed website is conducted by analyzing the land lease data before and after implementing the system, using the Overall Equipment Effectiveness (OEE) method to measure the Availability Rate, Performance Efficiency, and Quality of Product, resulting in more objective outcomes compared to similar research. The results and conclusions of this research indicate that the web-based Telco Tower Land Lease Information System is an effective solution for the management and leasing of land for telecommunication towers. In the performance test of the analytical system, the obtained values were 100% for Availability Rate, 99.69% for Performance Efficiency, and 100% for Quality of Product. Thus, the Overall Equipment Effectiveness (OEE) value obtained is 99.69%, surpassing the World Class OEE standard of 85%.